Рус-Бухоро урушларидаги ҳарбий ҳаракатлар тарихининиг манбаларда ёритилиши - Каландарова, Ф.А (SCIENCE and SOCIETY, 2023)
This article examines the military operations in the Russian-Bukhara wars and their coverage in local sources. Also, in
Keywords: Ahmad Danish; Mirza Sami; Mirza Salimbek; Maydayulgun; Sassiqkul; Chuponota